Factors influencing pre-eclampsia/eclampsia outcomes in high-risk patients in Zimbabwe - C Mudokwenuy-Rawdon; M C Bezuidenhout; V J Ehlers (AOSIS, 2003)
Severe pre-eclampsia/eclampsia remains one of the major causes of maternal mortality in Zimbabwe. Opsomming Ernstige pre-eklampsie/eklampsie bly een van die hoofoorsake van moederlike sterftes in Zimbabwe. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.